Acousto-optic modulation of light polarisation in monoclinic crystals. (April 2021) - Chizhikov, A.I.; Naumenko, N.F.; Yushkov, K.B.; Molchanov, V.Ya.; Pavlyuk, A.A.
Abstract: A configuration of a laser polarisation modulator based on isotropic acousto-optic interaction is proposed. Polarisation control is performed by a 2D acousto-optic cell based on one monoclinic single crystal. A possibility of implementing this modulator on the basis of a KY(WO4 )2 crystal is demonstrated.